"State, nation and democracy" - "Basu, Partha Pratim (ed.)" (New Delhi, 2007)
Essays on India, Indonesia, China, Muanmar, global issues, terrorism, foreign policy particularly from South Asian perspective
Keywords: Democracy-Congress